Soul Over Lightning : Poems - Gonzalez, Ray (Book collections on Project MUSE., 2014)
In this collection, which the poet calls his "rebirth in the search for home," Ray Gonzalez expresses the gentle, humble intelligence that has made him a leading voice in Latino letters. He shares with the reader the voice of a soul searcher who has passed through middle age and still vibrates with passion for the world. Gonzalez shows his profound respect for other people, species, places, elements, and histories. Illusions to religious imagery knock against those of the natural world-feathers and rocks-creating a complex tableau of objects and feelings. Employing the image-driven approach for.